Of fish, pigs and cesspits : a comparative study of stable carbon and nitrogen isotope analyses on animal bone and soil samples from five medieval sites in Belguim - Schietecatte, Liesbet (Department of Archaeology, 2014)
Bibliography: leaves 141-184.